FAMILY CONTROL, INSTITUTIONAL OWNERSHIP, AND DIVIDEND POLICY OF MANUFACTURING COMPANIES LISTED IN INDONESIA STOCK EXCHANGE - Madyan, Muhammad; Meidiaswati, Harlina; Sasikirono, Nugroho; Herlambang, Muhammad Hadyan (Jurnal Reviu Akuntansi dan Keuangan)
This study is conducted to examine the effect of family share ownership on the dividend policy of manufacturing companies in the Indonesia Stock Exchange (IDX). In this study, we also examine the moderating effect of institutional ownership on the relationship between family ownership and dividend policy. The number of observations 137 firm-years, consisting of family companies in the manufacturing sector listed on the IDX in the period 2013-2016. The test results show that family ownership has a positive effect on the dividend payout ratio. Research also shows that institutional ownership weakens the relationship between family ownership and dividend payout ratio.